A Single Case Study on the Curative Effect of Some Ayurvedic Modalities in Kati Prista Graha w.s.r Ankylosing Spondylitis - Mahapatra, PB Kar; Nematullah, Md; Mahmood, Sufia; Das, Madhumita (International Research Journal of Ayurveda & Yoga, 2022)
Ankylosing spondylitis is a most troublesome health hazards all over globe the patient of this gradually become physically challenged and mentally depressed. There are no such safe and effective remedy in modern medicine whereas Ayurvedic treatment has showed an excellent curative effect in a case of Ankylosing spondylitis with HLA-B27 positive. As Ayurveda usually delt with most of the neuro-musculo-skeletal disorder in a significant success manner through the conceptual remedies of Vata Vyadhi. In present study a 28-year-old young boy become bedridden by the ailment Ankylosing spondylitis with the evidence of HLA-B27 positive, some Panchakarma therapy along with Snehana and Swedana and internal Ayurvedic medicine have been implied to the patient that showed new ray of life to the patient by relieving the complaints and presenting the negative report of HLA-B27.